Influence of leptin administration to pregnant mice on fetal gene expression and adaptation to sweet and fatty food in adult offspring of different sexes - E. I. Denisova; E. N. Makarova (Вавиловский журнал генетики и селекции)
Elevated leptin in pregnant mice improves metabolism in offspring fed high-calorie diet and its influence may be sex-specific. Molecular mechanisms mediating leptin programming action are unknown. We aimed to investigate programming actions of maternal leptin on the signaling function of the placenta and fetal liver and on adaptation to high-calorie diet in male and female offspring. Female C57BL/6J mice received leptin injections in mid-pregnancy. Gene expression was assessed in placentas and in the fetal brain and liver at the end of pregnancy. Metabolic parameters and gene expression in the liver, brown fat and hypothalamus were assessed in adult male and female offspring that had consumed sweet and fatty diet (SFD: chow, lard, sweet biscuits) for 2 weeks. Females had lower blood levels of leptin, glucose, triglycerides and cholesterol than males. Consuming SFD, females had increased Ucp1 expression in brown fat, while males had accumulated fat, decreased blood triglycerides and liver Fasn expression. Leptin administration to mothers increased Igf1 and Dnmt3b expression in fetal liver, decreased post-weaning growth rate, and increased hypothalamic Crh expression in response to SFD in both sexes. Only in male offspring this administration decreased expression of Fasn and Gck in the mature liver, increased fat mass, blood levels of glucose, triglycerides and cholesterol and Dmnt3a expression in the fetal liver. The results suggest that the influence of maternal leptin on the expression of genes encoding growth factors and DNA methyltransferases in the fetal liver may mediate its programming effect on offspring metabolic phenotypes.